2014
DOI: 10.1016/j.acvd.2014.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Anterior-posterior versus anterior-lateral electrode position for external electrical cardioversion of atrial fibrillation: A meta-analysis of randomized controlled trials

Abstract: The present analysis suggests that only patients with a left atrium diameter≤45 mm and lone atrial fibrillation might derive benefits from the anterior-posterior electrode position compared with the anterior-lateral electrode position during external electrical cardioversion for atrial fibrillation. However, there was insufficient evidence to support any advantages for the anterior-posterior electrode position in other situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 24 publications
0
18
0
1
Order By: Relevance
“…Although some studies have shown that antero-posterior electrode placement is more effective than the traditional antero-apical position in elective cardioversion of atrial fibrillation, 439,440 the majority have failed to demonstrate any clear advantage of any specific electrode position. [441][442][443][444] Efficacy of cardioversion may be less dependent on electrode position when using biphasic impedance-compensated waveforms. [443][444][445] The following electrode positions all appear safe and effective for cardioversion of atrial arrhythmias:…”
Section: Electrode Positionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some studies have shown that antero-posterior electrode placement is more effective than the traditional antero-apical position in elective cardioversion of atrial fibrillation, 439,440 the majority have failed to demonstrate any clear advantage of any specific electrode position. [441][442][443][444] Efficacy of cardioversion may be less dependent on electrode position when using biphasic impedance-compensated waveforms. [443][444][445] The following electrode positions all appear safe and effective for cardioversion of atrial arrhythmias:…”
Section: Electrode Positionmentioning
confidence: 99%
“…[441][442][443][444] Efficacy of cardioversion may be less dependent on electrode position when using biphasic impedance-compensated waveforms. [443][444][445] The following electrode positions all appear safe and effective for cardioversion of atrial arrhythmias:…”
Section: Electrode Positionmentioning
confidence: 99%
“…reported on the use of ice crystals (of different size) to form pores in collagen scaffolds; a 3D scaffold with a gradient of micrometer‐sized (150–500 µm) pores could be obtained. [ 92 ]…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…A recent large meta‐analysis did not demonstrate a difference in cardioversion success rates for different electrode positions (anteroposterior [AP] vs anteroapical [AA]) in most patients . However, this did not specifically examine electrode positions in obese patients.…”
Section: Introductionmentioning
confidence: 98%